Fantasy and Dread: The Demand for Information and the Consumption Utility of the Future - Ganguly, Ananda; Tasoff, Joshua (Management Science, 2017)
We present evidence that intrinsic demand for information about the future is increasing in expected future consumption utility. In the first experiment, subjects may resolve a lottery now or later. The information is useless for decision making, but the larger the reward, the more likely subjects are to pay to resolve the lottery early. In the second experiment, subjects may pay to avoid being tested for herpes simplex virus type 1 (HSV-1) and the more highly feared type 2 (HSV-2). Subjects are three times more likely to avoid testing for HSV-2, suggesting that more aversive outcomes lead to more information avoidance. In a third experiment, subjects make choices about when to get tested for a fictional disease. Some subjects behave in a way consistent with expected utility theory, and others exhibit greater delay of information for more severe diseases. We also find that information choice is correlated with positive affect, ambiguity aversion, and time preference, as some theories predict. Data, as supplemental material, are available at https://doi.org/10.1287/mnsc.2016.2550 . This paper was accepted by Teck-Hua Ho, behavioral economics.